Den tværmediale serialitet: Fra kriseramte superhelte til tankefulde androider - Kannik Haastrup, Helle (Passage - Tidsskrift for litteratur og kritik, 2018)
This study investigates how serial storytelling in fiction film and television drama are connected through transmedia relations with a focus on aesthetics and the analysis of narrative, character and title sequences and how they are establishing seriality. The analysis is concerned with two main tendencies apparent in contemporary media culture representing different forms of transmedia seriality: ‘multi-protagonist transmedia storytelling’ as it unfolds in the Marvel fictional universe between the film series and the tv-series and ‘the mind game serial drama’ in the tv-series Westworld with connections to the official website and social media.